The anti‐sigma factor MucA is required for viability in Pseudomonas aeruginosa. Issue 2 (18th May 2021) - Schofield, Melissa C.; Rodriguez, Daniela Q.; Kidman, Amanda A.; Cassin, Erin K.; Michaels, Lia A.; Campbell, Elizabeth A.; Jorth, Peter A.; Tseng, Boo Shan
Abstract: During decades‐long infections in the cystic fibrosis (CF) airway, Pseudomonas aeruginosa undergoes selection. One bacterial genetic adaptation often observed in CF isolates is mucA mutations. MucA inhibits the sigma factor AlgU. Mutations in mucA lead to AlgU misregulation, resulting in a mucoid phenotype that is associated with poor CF disease outcomes. Due to its ability to be mutated, mucA is assumed to be dispensable for bacterial viability. Here we show that, paradoxically, a portion of mucA is essential in P. aeruginosa . We demonstrate that mucA is no longer required in a strain lacking algU, that mucA alleles encoding for proteins that do not bind to AlgU are insufficient for viability, and that mucA is no longer essential in mutant strains containing AlgU variants with reduced sigma factor activity. Furthermore, we found that overexpression of algU prevents cell growth in the absence of MucA, and that this phenotype can be rescued by the overproduction of RpoD, the housekeeping sigma factor. Together, these results suggest that in the absence of MucA, the inability to regulate AlgU activity results in the loss of bacterial viability. Finally, we speculate that the essentiality of anti‐sigma factors that regulate envelope function may be a widespread phenomenon in bacteria. Abstract : The opportunistic pathogen Pseudomonas aeruginosa forms chronic infections in the lungs of cystic fibrosis (CF) patients. In clinical settings, mutations often arise in the gene mucA of P . aeruginosa, which result in mucoid cells and are associated with poor disease outcomes in these patients. Our study explores the paradox of mucA essentiality, which we show is due to the required regulation of AlgU, its cognate sigma factor that activates the envelope stress response. ​